A Molten‐Salt Method to Synthesize Co9S8 Embedded, N, S Co‐Doped Mesoporous Carbons from Melamine Formaldehyde Resins for Electrocatalytic Hydrogen Evolution Reactions. Issue 5 (5th May 2022) - Miao, Sijia; Xu, Jing; Cui, Chengzhe; Tang, Duihai; Zhang, Wenting; Xin, Shigang; Zhao, Zhen
Abstract: We developed a molten salts process to prepare Co9 S8 nanoparticles (NPs) entrapped, S, N co‐doped carbons. Cobalt chloride was used as the cobalt source. The melamine‐formaldehyde (MF) resin provided the carbon source and nitrogen source, and thiourea provided sulfur source. In addition, common inorganic salts were added as templates to generate pores. The characterization results showed that the prepared materials contained high contents of N, S and Co, and were mesoporous composites. At the same time, the porosity of electrocatalyst depended on the type of salt and the mass ratio of precursor to salt, which further affected the electrocatalytic activity of hydrogen evolution reaction (HER). The best prepared catalyst showed excellent HER performance. The onset overpotential of the catalyst was low (33 mV) and had a small Tafel slope (61.1 mV dec −1 ), in addition to good stability in alkaline media. Abstract : A molten salts process was developed to prepare Co9 S8 nanoparticles entrapped, S, N co‐doped carbons. CoCl2 was used as the cobalt source. The melamine‐formaldehyde resin provided the carbon and nitrogen source, and thiourea provided sulfur source. Common salts were added as templates to generate pores. The best catalyst showed excellent HER performance. The onset overpotential of the catalyst was low (33 mV) and had a small Tafel slope (61.1 mV dec −1 ), in addition to good stability in alkaline media.